Introduction to Microsoft Power BI (Video) - Sorensen, Chris (Microsoft Press, 2021)
Sneak Peek The Sneak Peek program provides early access to Pearson video products and is exclusively available to Safari subscribers. Content for titles in this program is made available throughout the development cycle, so products may not be complete, edited, or finalized, including video post-production editing. 7+ Hours of Video Instruction Discover how you can use Power BI to help your organization to become more data driven. Whether you are new to analytics or have been stuck preparing and delivering data using legacy BI tools, this video shows you how to use Microsoft Power BI with confidence. In this video, learn ways to import data from various sources as well as how to transform and cleanse data prior to loading it to a report-ready, self-service-enabled data model. Create visualizations in the Power BI Desktop and then secure, share, and collaborate using the various features in the Power BI service. Using his years of experience teaching Power BI to a variety of learners, Microsoft Certified Trainer Chris Sorensen explains the core concepts of Power BI to expose you to the most widely used features and functions in Power BI. He carefully explains the "why" behind using those features, not just the "how." In his engaging style grounded in real-world scenarios, Chris gives you the confidence to navigate and build effective Power BI solutions, quickly and effectively. Build good habits and develop in your career as a business analyst or data-driven business user. About the Instructor Chris Sorensen CPA, CGA, is the Founder and President of Iteration Insights, a tech-enabled data analytics solutions provider based in Calgary, Alberta. In his career, he has led numerous Analytics projects in more than 15 industries across small to enterprise-sized organizations. He is a Microsoft Certified Data Analyst Associate and Microsoft Certified Trainer with a combined 20+ years of industry-solution delivery and teaching experience. He has evangelized both Excel and Power BI with Microsoft since July 2015 and is the author of the Microsoft Press Exam Ref 70-779 Analyzing and Visualizing Data with Microsoft Excel and co-author of Data Analysis Fundamentals with Excel (Video) published by Microsoft Press. Skill Level Beginner-Intermediate Learn How To Import and transform data in Power Query Editor Build a data model that supports self-service analysis Develop reports and visualizations using the Power BI Desktop Enhance the experi ...
Online resource; Title from title screen (viewed May 14, 2021)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos